Destination Brand Personality of Portugal for the Russian-Speaking Market - Chaykina, Taisiya; Guerreiro, Manuela; Mendes, Júlio (Journal of Tourism, Sustainability and Well-being, 2014)
Nowadays brand personality is admitted to be one of the essential parts of brand strategy. It has also become a popular aspect of destination branding due to the fact that destinations are constantly competing for visitors attention in various ways. The term of branding has been first applied to marketing of services or places since the 1990’s. Later on it was broadened and utilized by specialists in the field of tourism marketing. Tourism brand personality is a relatively new one and there are only few works devoted to brand personality of countries as tourism destinations. Keeping in mind the novelty of the research area, this study was planned as exploratory in nature. The stated goal of the research is: to identify the brand personality attributes ascribed to Portugal by the Russian-speaking market and compare the possible existing differences of attributes among the subgroups of the study (actual visitors and possible future visitors). The results of this research might be interesting to the local officials and to business representatives as it highlights the main attributes of Portugal brand personality from the Russian speaking people’s point of view.